Relationship between Years of Service and Dimensions of Organizational Citizenship Behavior in Peruvian Operators: A Convergent Network Analysis - Flores-Torres, Betsy Lucerito (2024)
The aim of this research was to examine the relationship between the dimensions of organizational citizenship behavior and years of service in a balanced sample of 150 employees, comprised of 55.3 % men and 44.7 % women. The majority of the participants were young, with 49.3 % between the ages of 18 and 30. The results reveal a dynamic and stable network, highlighting that Altruism and Civic Virtue show the strongest correlation (r = .38), suggesting that a strong commitment to organizational goals promotes altruistic behaviors. In contrast, Years of Service and Altruism present a significant negative correlation (r = -.31), indicating that employees with less seniority tend to exhibit greater altruism. In terms of centrality indices, Sportsmanship stands out as the behavior with the greatest sum of weighted connections, suggesting a predominant role in influencing other behaviors. Additionally, Altruism not only shows a strong correlation with Civic Virtue but also has the greatest expected influence in the network, reflecting a generally positive impact. In conclusion, these findings provide a detailed view of how various behaviors influence work dynamics and offer valuable insights for human resource management in promoting a collaborative and positive work environment.